Novel high-temperature-resistant well cementation cement slurry system for myriameter deep well

A high-temperature resistant cementing slurry system for ultra-deep wells uses low-heat silicate cement and optimized materials to prevent abnormal gelation, ensuring stable performance and safety in ultra-high temperature environments.

CN119241175AActive Publication Date: 2025-01-03JIAHUA SPECIAL CEMENT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411402908.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Existing cementing technologies for ultra-deep wells face issues with abnormal gelation, poor slurry suspension stability, and rapid decline in cement stone strength due to ultra-high temperature and pressure conditions, affecting construction safety and long-term wellbore isolation quality.

Method used

A high-temperature resistant cementing slurry system composed of low-heat silicate cement, anti-abnormal gelling material, enhanced anti-decay material, suspended fluid loss reducing material, high-temperature fluid loss reducer, and high-temperature retarder, optimized with specific chemical compositions and particle sizes to inhibit abnormal gelation and maintain stability.

Benefits of technology

The system effectively prevents abnormal gelation and maintains stable performance of the cement slurry, ensuring safe and efficient cementing construction in ultra-deep wells by controlling hydration rates and reducing water loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241175A_ABST
    Figure CN119241175A_ABST
Patent Text Reader

Abstract

The invention discloses a novel high-temperature-resistant well cementation cement slurry system for a myriameter deep well, and relates to the technical field of well cementation materials for oil and gas well engineering. The well cementation cement slurry system is prepared from the following components in parts by weight: 100 parts of low-heat Portland cement, 10 to 20 parts of abnormal gelling prevention material, 35 to 55 parts of reinforced anti-declining material, 10 to 20 parts of suspended filtrate loss reduction material, 6 to 8 parts of high-temperature fluid loss agent and 2 to 5 parts of high-temperature retarder, wherein the abnormity-preventing cementing material comprises the following components in parts by weight: (40-60) parts of ulexite, (20-40) parts of broolerite, (10-20) parts of datolite and (5-15) parts of chalcanthite. The content of dicalcium silicate in cement components is limited, and the specific surface area of cement is reduced, so that the hydration rate of slurry in a high-temperature environment is relieved, the phenomenon that the cement slurry rapidly generates abnormal gelling is inhibited, and the abnormal gelling prevention material has a good anti-blocking effect from the perspective of cement hydration products. The abnormal gelling influence caused by fluctuation of cement mineral components in different batches on the cement paste is solved, and meanwhile, other performance of the paste can be stably controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementing materials for oil and gas well engineering, and more specifically to a new type of high temperature resistant cementing slurry system for 10,000-meter deep wells. Background Art

[0002] Deep and ultra-deep oil and gas resources have become an important area for increasing reserves and production in my country's oil and gas reservoirs. In the process of oil and gas well exploitation, cementing is a key engineering technology to ensure safe production throughout the life cycle of the wellbore and achieve efficient development. However, cementing of deep wells and even ultra-deep wells of 10,000 meters will face ultra-high temperature and ultra-high pressure working conditions, which can easily lead to abnormal gelation of cement slurry, poor slurry suspension stability, and rapid decline in cement stone strength, which in turn affects cementing construction safety and long-term wellbore isolation quality. Therefore, it is urgent to solve this series of problems in order to achieve stable control of the working performance of ultra-high temperature cement slurry system.

[0003] The existing technical means mainly adjust the working performance of cement slurry from the aspects of strength decay resistance and admixture synthesis optimization. For example, the application publication date is April 28, 2020, the application publication number is CN111072350A, and the invention patent application publication text named "A high temperature resistant cementing slurry system" specifically discloses that the system is composed of silicate cement: 60-75%; strength decay resistance agent: 15-25%; crystal stabilizer: 2-8%; high temperature retarder: 0.5-6%; high temperature fluid loss reducer: 3-8%. Mainly by adding crystal stabilizers, participating in the hydration reaction when the cement slurry is hydrated, metal ions enter the structure of hydrated calcium silicate, which prevents the transformation of tobermorite to xonotlite in the hydration product, so that the cement stone maintains a dense structure, thus having good high temperature stability.

[0004] For example, the application publication date is November 8, 2022, the application publication number is CN115304317A, and the invention patent application publication text named "A high-temperature strength-decay resistant oil well cement slurry system" specifically discloses that the system is composed of cementitious materials: 47.5wt% to 72.5wt%; silica sand: 15wt% to 25wt%; high-temperature strength-decay resistant material: 10wt% to 25wt%; high-temperature stabilizer: 2wt%; dispersant: 0.5wt%. It has the advantages of high-temperature strength-decay resistance and stable high-temperature performance, can effectively alleviate the strength-decay problem of cement stone under high-temperature conditions, and meet the requirements of oil and gas well cementing.

[0005] For another example, the publication date of the application is October 26, 2018, the application publication number is CN108706927A, and the invention patent application publication text entitled "A suspension stabilizer for high-temperature cement slurry and high-temperature resistant cement slurry prepared therefrom" specifically discloses that the suspension stabilizer is composed of 0.5 to 4 parts of fiber materials, 1 to 5 parts of surfactant powder materials, and 0.5 to 2 parts of flocculant powder materials. The high-temperature resistant cement slurry prepared using the suspension stabilizer has a low initial consistency and good sedimentation stability.

[0006] For another example, the application publication date is December 3, 2021, the application publication number is CN113736016A, and the invention patent application publication text named "High-temperature resistant polymer suspension stabilizer cement slurry for oil well cement and preparation method thereof" specifically discloses that the system is composed of silicate cement, silica fume, fluid loss reducer, retarder SD210, defoamer, slurry preparation water, and high-temperature resistant polymer suspension stabilizer. The disclosed high-temperature resistant suspension stabilizer can withstand high temperatures of up to 200°C, which can avoid a significant decrease in polymer viscosity due to high-temperature thermal degradation, thereby enhancing its high-temperature suspension ability.

[0007] In general, the above-mentioned technical means are mainly aimed at optimizing a specific problem faced by high-temperature cement slurry, and rarely take into account the overall performance of the cement slurry system. At the same time, there is also a lack of ideas to deal with the abnormal gelation phenomenon caused by high-temperature cement slurry. Therefore, it is difficult to ensure the stable performance control of cement slurry throughout the life cycle of the wellbore. Summary of the invention

[0008] In order to overcome the defects and shortcomings of the above-mentioned prior art, the present invention provides a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells. The purpose of the present invention is to solve the problem of abnormal gelation of high-temperature cement slurry, while at the same time achieving stable control of other properties of the slurry.

[0009] In order to solve the above problems existing in the prior art, the present invention is implemented through the following technical solutions.

[0010] The present invention provides a new high temperature resistant cementing slurry system for a 10,000-meter deep well. The cementing slurry system comprises the following components in parts by weight: 100 parts of low heat Portland cement; 10~20 parts of anti-abnormal gelling material; 35~55 parts of enhanced anti-recession materials; 10-20 parts of suspended fluid loss reducing materials; 6~8 parts of high temperature fluid loss reducer; 2~5 parts of high temperature retarder; The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m2 / kg, 7d hydration heat ≤250kJ / kg; The anti-abnormal gelling material comprises the following components in parts by weight: 40-60 parts of ulexite, 20-40 parts of colemanite, 10-20 parts of sylvite, and 5-15 parts of chalcanthite; the chemical composition requirements of the anti-abnormal gelling material for cementing slurry are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%; the particle fineness requirements of the anti-abnormal gelling material for cementing slurry are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0011] Further preferably, the purity of ulexite in the abnormality-preventing gelling material is required to be ≥90wt.%, and the chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%.

[0012] Further preferably, the purity of colemanite in the abnormal-preventing gelling material is required to be ≥90wt.%, and the chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%.

[0013] Further preferably, the purity of leonite in the abnormality-preventing gelling material is required to be ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%.

[0014] Further preferably, the purity of the gallstone in the anti-abnormal gelling material is required to be ≥90wt.%, and the chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0015] More preferably, the abnormal gelling material is obtained by processing through the following steps: S1. Mix 40-60 parts of ulexite, 20-40 parts of colemanite and 10-20 parts of boraxite evenly, crush them after mixing evenly, and control the crushing ratio to 40-70; grind the crushed mixed material into mixed fine material, and control the crushing ratio to 400-900; send the crushed mixed fine material to a high-temperature calcining furnace for calcination, and control the calcination temperature to 800°C-1500°C; the mixed material after calcination is quickly cooled to room temperature, and the cooling time is controlled to 10-20min; after cooling, obtain Class A mixed material; S2, mixing the Class A mixture prepared in step S1 with 5-15 parts of gallstones, and grinding the mixture to obtain a Class B mixture; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm; S3, subjecting the B-type mixed material to a coating treatment, specifically, adding the B-type mixed material to a coating solution, mixing evenly and reacting for a set time, and vacuum drying to obtain the abnormality-proof gelling material.

[0016] More preferably, the coating solution in step S3 comprises the following components by mass ratio: Anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = (55~70): (15~25): (5~10): (5~10): (5~10).

[0017] More preferably, the concentration of the plating solution in step S3 is 55 wt.% to 85 wt.%.

[0018] More preferably, in step S3, the usage ratio of the type B mixture to the plating solution is 1:(5-20).

[0019] More preferably, in step S3, the reaction time is set to 5-35 min; and the vacuum drying temperature is 35° C.-55° C.

[0020] Further preferably, the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = (80-90): (10-20).

[0021] More preferably, the composition of the quartz sand is SiO2≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of the metakaolin is Al2O3≥45wt.%, SiO2≥45 wt.%, and the powder fineness is ≥800 mesh.

[0022] Further preferably, the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio of ultrafine calcium carbonate: dolomite fine powder = (30-70): (30-70).

[0023] More preferably, the ultrafine calcium carbonate has a purity of ≥90wt.%, and a powder fineness of ≥800 mesh; the dolomite fine powder has a purity of ≥90wt.%, and a powder fineness of ≥1000 mesh.

[0024] Further preferably, the high temperature fluid loss additive is an AMPS anionic polymer.

[0025] Further preferably, the high temperature retarder is an AMPS copolymer system.

[0026] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows: 1. The present invention adopts low-heat silicate cement as the cement base material, and reduces the dicalcium silicate content in the cement component and the specific surface area of ​​the cement, thereby alleviating the hydration rate of the slurry under high temperature environment, and to a certain extent, can inhibit the rapid abnormal gelation of the cement slurry, which is beneficial to the adjustment of the slurry construction performance.

[0027] 2. The suspended fluid loss reducing material used in the present invention, on the one hand, utilizes the characteristics of the material such as small particle size, large specific surface area, and high surface activity to reduce the distance between solid phase particles in the cement slurry, thereby playing a role in viscosity increase and thickening; on the other hand, it utilizes the particle grading principle to improve the pore structure of the cement filter cake by "bridging" and blocking, etc., to form a thin and dense filter cake to achieve the purpose of reducing water loss.

[0028] 3. The anti-abnormal gelling material used in the present invention can solve the abnormal gelling effect on cement slurry caused by the fluctuation of cement mineral components in different batches from the perspective of cement hydration products.

[0029] The solution is as follows: different batches of cement have different tricalcium aluminate contents in their mineral components, and thus different aluminum ion contents in the cement slurry. Tricalcium aluminate hydrates very quickly, quickly forming hydrated calcium aluminate gel products in the cement slurry, causing abnormal gelation phenomena such as thickening of the cement slurry. In addition, when the aluminum ion concentration in the cement slurry reaches a certain level, it will combine and cross-link with the calcium ions and the polymer chains in the polymer admixture to form a mutually doped cross-linked network structure, causing abnormal gelation of the cement slurry (the thickening curve shows "bulging" and "core-encapsulation" phenomena). The abnormal gelling prevention material used in the present invention releases sulfate ions through a hydrolysis reaction, and reacts with aluminum ions and calcium ions under medium-high temperature hydrothermal conditions to generate monosulfur calcium sulfoaluminate. On the one hand, the aluminum ion content in the cement slurry is reduced, and aluminum ions are prevented from forming a mutually doped cross-linked network structure with other ions and high molecular chains in the polymer admixture; on the other hand, the monosulfur calcium sulfoaluminate is wrapped on the surface of tricalcium aluminate to prevent its rapid hydration, thereby preventing the rapid formation of hydrated calcium aluminate in the cement slurry, thereby preventing the cement slurry from abnormal gelling.

[0030] Therefore, no matter how the cement batches and their mineral components change, the main difference is the aluminum phase content in the cement components. The present technical means solves the abnormal gelling effect of aluminum ions on cement slurry from the root, so that the anti-abnormal gelling material of the present invention can adapt to different batches of cement.

[0031] 4. The anti-abnormal gelling material used in the present invention can effectively inhibit the abnormal gelling caused by the complexation between the admixture and the cement component. The working principle is: the polymer in the polymer admixture competes for the calcium ions in the cement slurry, and usually multiple polymer molecules chelate one calcium ion, thereby causing the long-chain polymer to form a bridge network, resulting in abnormal gelling of the cement slurry. The anti-abnormal gelling material used in the present invention releases borate ions and copper ions through a hydrolysis reaction. On the one hand, the copper ions will deprive the chelated calcium ions in the polymer molecules. Since the relative atomic mass of the copper ions is larger than that of the calcium ions, the copper ions will sink with the chelated polymer molecules in the cement slurry, thereby separating multiple polymer molecules; on the other hand, the borate ions will also rob the chelated calcium ions in the polymer molecules and preferentially form calcium borate. The calcium borate is quickly wrapped on the surface of tricalcium silicate and dicalcium silicate to prevent them from undergoing a hydration reaction, thereby prolonging the thickening time of the cement slurry. At this time, the deprived polymer molecules are evenly dispersed in the cement slurry in a flowing state, thereby inhibiting the high molecular long-chain polymer from forming a bridge network, thereby preventing the cement slurry from undergoing abnormal gelling.

[0032] 5. In the preparation of the abnormal-proof cementitious material, the Class B mixture is subjected to a coating treatment. The purpose is that the sulfate component in the Class B mixture will undergo a hydrolysis reaction during the cement slurry preparation process, and the released sulfate ions react with the aluminum ions and calcium ions in the cement slurry to form ettringite. Under low temperature conditions (generally below 70°C), ettringite is relatively stable. A large amount of water is consumed during the formation process of ettringite. At the same time, the needle-shaped ettringite is interlaced with each other, which can easily cause the cement slurry to thicken rapidly in a short period of time (mainly manifested in the "bulging" phenomenon on the cementing cement slurry thickening curve), which seriously affects the safety of cementing construction. Therefore, a coating method is adopted to form a layer of plastic resin protective film on the surface of Class B mixture particles. Under low temperature conditions, it can effectively prevent the sulfate component in Class B mixture from reacting with water, reduce the concentration of sulfate ions in the cement slurry, and thus prevent the formation of calcium sulfonate. At this time, Class B mixture is evenly dispersed in the cement slurry as a filling material. As the temperature rises during the grouting process, the resin protective film begins to decompose (generally above 70°C), and Class B mixture begins to hydrolyze. Although the sulfate ion concentration in the cement slurry will increase at this time, the generated calcium sulfonate is extremely unstable in medium and high temperature environments and will decompose rapidly, which will not cause the cementing cement slurry to thicken rapidly, thereby ensuring the smooth progress of cementing construction.

[0033] 6. The coating solution used in the preparation of the abnormal gelling prevention material in the present invention can be selected from existing commonly used coating solutions, as long as a plastic resin protective film can be formed on the surface of the Class B mixed material particles, and the resin protective film can be decomposed above 70° C. As a preferred embodiment of the present invention, the coating solution used in the present invention includes anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate compounded according to a set ratio, and its constituent monomers and ratios are optimal.

[0034] 7. The present invention limits and optimizes the chemical composition, fineness and purity of each material in the system. On the one hand, it ensures that the various properties of the cementing slurry system obtained after the materials are compounded meet the expected requirements. On the other hand, it can improve the compounding success rate of the cement slurry system and bring out the best performance of each material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a graph showing the test results of the cement slurry system thickening curve provided in Example 1 of the present invention; Figure 2 This is a graph showing the test results of the cement slurry system thickening curve provided in Comparative Example 1 of the present invention; Figure 3 is a graph showing the test results of the cement slurry system thickening curve provided in Example 2 of the present invention; Figure 4 is a graph showing the test results of the cement slurry system thickening curve provided in Example 3 of the present invention; Figure 5 is a graph showing the test results of the cement slurry system thickening curve provided in Example 4 of the present invention; Figure 6 This is a graph showing the test results of the cement slurry system thickening curve provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The following examples are all prepared cement slurries according to GB / T 19139-2012 standard. In the cement slurry system listed in the examples, low heat silicate cement is provided by Jiahua Special Cement Co., Ltd., the raw materials used in the enhanced anti-decay material and suspended fluid loss material can be purchased from the market, and the high temperature fluid loss agent and high temperature retarder are provided by Puyang Zhenghe Petroleum Engineering Technology Co., Ltd. The liquid-to-solid ratio of the cement slurry system is 0.44 .

[0038] Example 1 As a preferred embodiment of the present invention, this embodiment discloses a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells, including the following components by weight: 100 parts of low-heat silicate cement, 10 parts of anti-abnormal gelling material, 35 parts of enhanced anti-decay material, 10 parts of suspended filtration loss reducing material, 6 parts of high-temperature fluid loss reducing agent, 2 parts of high-temperature retarder, and 60 parts of water.

[0039] The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = 80:20; the composition of SiO2 in the quartz sand is ≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of Al2O3 in the metakaolin is ≥45wt.%, SiO2 ≥45 wt.%, and the powder fineness is ≥800 mesh; the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio is ultrafine calcium carbonate: dolomite fine powder = 30:70; the purity of the ultrafine calcium carbonate is ≥90wt.%, and the powder fineness is ≥800 mesh; the purity of the dolomite fine powder is ≥90wt.%, and the powder fineness is ≥1000 mesh; the high-temperature fluid loss reducing agent is an AMPS anionic polymer; the high-temperature retarder is an AMPS copolymer system; The abnormal gelling material includes the following components in parts by weight: 60 parts of ulexite, 25 parts of colemanite, 10 parts of leonite and 5 parts of chalcanthite.

[0040] In this embodiment, the abnormal gelling material is prepared by the following preparation method: S1. 60 parts by weight of ulexite, 25 parts by weight of colemanite and 10 parts by weight of boraxite are uniformly mixed, and then crushed by a grinding mill, with the crushing ratio controlled at 60; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 700; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 1350°C, and the mixed material after calcination is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 20min to obtain a Class A mixed material.

[0041] S2. Mix the Class A mixture prepared in step S1 with 5 parts by weight of gallstones and send it to a ball mill for grinding. After grinding, a Class B mixture is obtained; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0042] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 500 parts by weight of a coating solution having a concentration of 80 wt.%, mixed evenly and reacted for 5 minutes, and then placed in a 35° C. vacuum drying oven for drying to obtain the abnormal-proof gelling material.

[0043] The chemical composition requirements of the above-mentioned anti-abnormal gelling material are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.

[0044] As an example, in order to achieve the chemical composition requirements of the above-mentioned anti-abnormal cementing material, it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0045] In this embodiment, when preparing the anti-abnormal gelling material, the coating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 65:15:10:5:5.

[0046] Example 2 As a preferred embodiment of the present invention, this embodiment discloses a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells, including the following components by weight: 100 parts of low-heat silicate cement, 13 parts of anti-abnormal gelling material, 40 parts of enhanced anti-decay material, 13 parts of suspended filtration loss reducing material, 6.5 parts of high-temperature fluid loss reducing agent, 2.5 parts of high-temperature retarder, and 64 parts of water.

[0047] The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = 83:17; the composition of SiO2 in the quartz sand is ≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of Al2O3 in the metakaolin is ≥45wt.%, SiO2 ≥45 wt.%, and the powder fineness is ≥800 mesh; the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio is ultrafine calcium carbonate: dolomite fine powder = 40:60; the purity of the ultrafine calcium carbonate is ≥90wt.%, and the powder fineness is ≥800 mesh; the purity of the dolomite fine powder is ≥90wt.%, and the powder fineness is ≥1000 mesh; the high-temperature fluid loss reducing agent is an AMPS anionic polymer; the high-temperature retarder is an AMPS copolymer system; The abnormal gelling material includes the following components in parts by weight: 40 parts of ulexite, 35 parts of colemanite, 20 parts of leonite and 5 parts of chalcanthite.

[0048] In this embodiment, the abnormal gelling material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 35 parts by weight of colemanite and 20 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 65; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 750; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcination, with the calcination temperature controlled at 1200°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 15min to obtain a Class A mixed material.

[0049] S2. Mix the Class A mixture prepared in step S1 with 5 parts by weight of gallstones and send it to a ball mill for grinding. After grinding, a Class B mixture is obtained; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0050] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 1000 parts by weight of a 75wt.% coating solution, mixed evenly and reacted for 10 minutes, and then placed in a 40°C vacuum drying oven for drying to obtain the abnormality-proof gelling material.

[0051] The chemical composition requirements of the above-mentioned anti-abnormal gelling material are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.

[0052] As an example, in order to achieve the chemical composition requirements of the above-mentioned anti-abnormal cementing material, it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0053] In this embodiment, when preparing the anti-abnormal gelling material, the coating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate, and the mass ratio is anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 55:20:8:10:7.

[0054] Example 3 As a preferred embodiment of the present invention, this embodiment discloses a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells, including the following components by weight: 100 parts of low-heat silicate cement, 15 parts of anti-abnormal gelling material, 45 parts of enhanced anti-decay material, 15 parts of suspended filtration loss reducing material, 7 parts of high-temperature fluid loss reducing agent, 3 parts of high-temperature retarder, and 67 parts of water.

[0055] The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = 85:15; the SiO2 in the quartz sand is ≥98 wt.%, and the powder fineness is ≥325 mesh; the Al2O3 in the metakaolin is ≥45wt.%, SiO2 ≥45 wt.%, and the powder fineness is ≥800 mesh; the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio is ultrafine calcium carbonate: dolomite fine powder = 50:50; the purity of the ultrafine calcium carbonate is ≥90wt.%, and the powder fineness is ≥800 mesh; the purity of the dolomite fine powder is ≥90wt.%, and the powder fineness is ≥1000 mesh; the high-temperature fluid loss reducing agent is an AMPS anionic polymer; the high-temperature retarder is an AMPS copolymer system; The abnormal gelling material includes the following components in parts by weight: 40 parts of ulexite, 35 parts of colemanite, 10 parts of leonite and 15 parts of chalcanthite.

[0056] In this embodiment, the abnormal gelling material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 35 parts by weight of colemanite and 10 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 70; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 800; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 1000°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, with the cooling time controlled at 10min, to obtain a Class A mixed material.

[0057] S2. Mix the Class A mixture prepared in step S1 with 15 parts by weight of gallstones, and then send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0058] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 1500 parts by weight of a 70wt.% coating solution, mixed evenly and reacted for 15 minutes, and then placed in a 45°C vacuum drying oven for drying to obtain the abnormal-proof gelling material.

[0059] The chemical composition requirements of the above-mentioned anti-abnormal gelling material are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.

[0060] As an example, in order to achieve the chemical composition requirements of the above-mentioned anti-abnormal cementing material, it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0061] In this embodiment, when preparing the anti-abnormal gelling material, the coating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate, and the mass ratio is anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 55:25:10:5:5.

[0062] Example 4 As a preferred embodiment of the present invention, this embodiment discloses a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells, including the following components by weight: 100 parts of low-heat silicate cement, 17 parts of anti-abnormal gelling material, 50 parts of enhanced anti-decay material, 17 parts of suspended filtration loss reducing material, 7.5 parts of high-temperature fluid loss reducing agent, 4 parts of high-temperature retarder, and 69 parts of water.

[0063] The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = 88:12; the composition of SiO2 in the quartz sand is ≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of Al2O3 in the metakaolin is ≥45wt.%, SiO2 ≥45 wt.%, and the powder fineness is ≥800 mesh; the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio is ultrafine calcium carbonate: dolomite fine powder = 60:40; the purity of the ultrafine calcium carbonate is ≥90wt.%, and the powder fineness is ≥800 mesh; the purity of the dolomite fine powder is ≥90wt.%, and the powder fineness is ≥1000 mesh; the high-temperature fluid loss reducing agent is an AMPS anionic polymer; the high-temperature retarder is an AMPS copolymer system; The abnormal gelling material includes the following components in parts by weight: 50 parts of ulexite, 20 parts of colemanite, 15 parts of leonite and 15 parts of chalcanthite.

[0064] In this embodiment, the abnormal gelling material is prepared by the following preparation method: S1. 50 parts by weight of ulexite, 20 parts by weight of colemanite and 15 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 40; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, with the crushing ratio controlled at 400; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, with the calcining temperature controlled at 800°C, and the calcined mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 10min to obtain a Class A mixed material.

[0065] S2. Mix the Class A mixture prepared in step S1 with 15 parts by weight of gallstones, and then send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0066] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 2000 parts by weight of a 55wt.% coating solution, mixed evenly and reacted for 25 minutes, and then placed in a 50°C vacuum drying oven for drying to obtain the abnormality-proof gelling material.

[0067] The chemical composition requirements of the above-mentioned anti-abnormal gelling material are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.

[0068] As an example, in order to achieve the chemical composition requirements of the above-mentioned anti-abnormal cementing material, it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0069] In this embodiment, when preparing the anti-abnormal gelling material, the coating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate. By mass ratio, anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 70:15:5:5:5.

[0070] Example 5 As a preferred embodiment of the present invention, this embodiment discloses a new type of high-temperature resistant cementing slurry system for 10,000-meter deep wells, including the following components by weight: 100 parts of low-heat silicate cement, 20 parts of anti-abnormal gelling material, 55 parts of enhanced anti-decay material, 20 parts of suspended filtration reduction material, 8 parts of high-temperature fluid loss reducer, 5 parts of high-temperature retarder, and 73 parts of water.

[0071] The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; the enhanced anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = 90:10; the composition of SiO2 in the quartz sand is ≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of Al2O3 in the metakaolin is ≥45wt.%, SiO2 ≥45 wt.%, and the powder fineness is ≥800 mesh; the suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio is ultrafine calcium carbonate: dolomite fine powder = 70:30; the purity of the ultrafine calcium carbonate is ≥90wt.%, and the powder fineness is ≥800 mesh; the purity of the dolomite fine powder is ≥90wt.%, and the powder fineness is ≥1000 mesh; the high-temperature fluid loss reducing agent is an AMPS anionic polymer; the high-temperature retarder is an AMPS copolymer system; The abnormal gelling material includes the following components in parts by weight: 40 parts of ulexite, 40 parts of colemanite, 10 parts of leonite and 10 parts of chalcanthite.

[0072] In this embodiment, the abnormal gelling material is prepared by the following preparation method: S1. 40 parts by weight of ulexite, 40 parts by weight of colemanite and 10 parts by weight of sylvite are mixed evenly, and then crushed by a grinding mill, with the crushing ratio controlled at 50; the crushed mixed material is sent to a ball mill for grinding into a mixed fine material, and the crushing ratio is controlled at 900; then the crushed mixed fine material is sent to a high-temperature calcining furnace for calcining, and the calcining temperature is controlled at 1500°C. After the calcination, the mixed material is quickly cooled to room temperature by a cooler, and the cooling time is controlled at 20min to obtain a Class A mixed material.

[0073] S2. Mix the Class A mixture prepared in step S1 with 10 parts by weight of gallstones and send it to a ball mill for grinding to obtain a Class B mixture. The particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

[0074] S3. The Class B mixture is subjected to coating treatment, specifically, 100 parts by weight of the Class B mixture is added to 1500 parts by weight of a coating solution having a concentration of 85 wt.%, mixed evenly and reacted for 35 minutes, and then placed in a 55° C. vacuum drying oven for drying to obtain the abnormal-proof gelling material.

[0075] The chemical composition requirements of the above-mentioned anti-abnormal gelling material are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%.

[0076] As an example, in order to achieve the chemical composition requirements of the above-mentioned anti-abnormal cementing material, it can be achieved by limiting the purity and chemical composition of ulexite, colemanite, sylvasite and chalcanthite, that is, the selection of ulexite, colemanite, sylvasite and chalcanthite materials. Specifically, the purity requirement of ulexite is ≥90wt.%, and its chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%; the purity requirement of colemanite is ≥90wt.%, and its chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%; the purity requirement of sylvasite is ≥90wt.%, and its chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%; the purity requirement of chalcanthite is ≥90wt.%, and its chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

[0077] In this embodiment, when preparing the anti-abnormal gelling material, the coating solution used is composed of anhydrous ethanol, phenolic resin, polymethyl methacrylate, dimethyl phthalate and diethyl phthalate, and the mass ratio is anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = 60:15:8:7:10.

[0078] Comparative Example 1 Compared with Example 1, the cement slurry system in this comparative example does not add anti-abnormal gelling material, and the formula is: 100 parts by weight of low-heat silicate cement + 35 parts by weight of reinforcing anti-decay material + 10 parts by weight of suspended fluid loss reducing material + 6 parts by weight of high-temperature fluid loss reducing agent + 2 parts by weight of high-temperature retarder + 56 parts by weight of water.

[0079] According to GB / T 19139-2012 standard, the engineering properties and mechanical properties of the cement slurry systems obtained in Examples 1 to 5 and Comparative Example 1 were tested. The test results are shown in Table 1.

[0080] Table 1 Test results of engineering properties and mechanical properties of high temperature cementing slurry system Note: The curing conditions for the upper and lower density difference experiment are: 260℃×20.7MPa×48h, the free liquid content test conditions are: 90℃×0.1MPa×2h, the API water loss test conditions are: 215℃×6.9MPa×30min, the cement paste compressive strength curing conditions are: 260℃×20.7MPa, and the thickening test conditions are: 215℃×125MPa×120min.

[0081] It can be seen from the engineering performance test results in Table 1 that the cementing slurry systems prepared in Examples 1 to 5 of the present invention have the advantages of good fluidity, zero free liquid content, low API water loss, good suspension stability, linearly adjustable thickening time, and no abnormal gelation phenomenon during the thickening process, and all meet the industry standard requirements of high-temperature cementing cement.

[0082] It can be seen from the mechanical property test results in Table 1 that the cement paste formed by curing the cement slurry system prepared in Examples 1 to 5 of the present invention has the advantages of high compressive strength at high temperatures and no decay, and meets the long-term sealing requirements of high-temperature deep wells.

[0083] Refer to the instruction manual Figure 1 and attached Figure 2 As shown, compared with Example 1, the cementing cement slurry system prepared in Comparative Example 1 exhibits serious abnormal gelation during the thickening process, which is specifically manifested as: the linear mutation value of the consistency exceeds 10Bc (obvious bulge appears on the curve), and the temperature curve fluctuates severely (obvious core coating appears on the thickening blade), indicating that the cement slurry system without adding the anti-abnormal gelling material of the present invention is difficult to ensure the stability of the high-temperature cement slurry thickening performance, thereby affecting the safety of cementing construction.

[0084] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells, characterized by: The cementing slurry system comprises the following components by weight: 100 parts of low heat Portland cement; 10~20 parts of anti-abnormal gelling material; 35~55 parts of enhanced anti-recession materials; 10-20 parts of suspended fluid loss reducing materials; 6~8 parts of high temperature fluid loss reducer; 2~5 parts of high temperature retarder; The C2S content of the low-heat silicate cement is ≥45 wt.%, and the specific surface area is controlled at 260-300m 2 / kg, 7d hydration heat ≤250kJ / kg; The anti-abnormal gelling material comprises the following components in parts by weight: 40-60 parts of ulexite, 20-40 parts of colemanite, 10-20 parts of sylvite, and 5-15 parts of chalcanthite; the chemical composition requirements of the anti-abnormal gelling material for cementing slurry are: 37wt.%<B2O3≤55wt.%, 11wt.%<CaO≤21wt.%, 5wt.%<SiO2≤13wt.%, 6wt.%<Na2O≤12wt.%, 1wt.%<SO3≤6wt.%, 1wt.%<CuO≤6wt.%; the particle fineness requirements of the anti-abnormal gelling material for cementing slurry are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm.

2. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 1, characterized in that: The purity of ulexite in the anti-abnormal gelling material is required to be ≥90wt.%, and the chemical composition requirements are: Na2O>6wt.%, CaO>12wt.%, B2O3>38wt.%.

3. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 1, characterized in that: The purity of the colemanite in the anti-abnormal cementitious material is required to be ≥90wt.%, and the chemical composition requirements are: CaO>18wt.%, B2O3>33wt.%.

4. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 1, characterized in that: The purity of the nautilus in the anti-abnormal gelling material is required to be ≥90wt.%, and the chemical composition requirements are: Na2O>22wt.%, SiO2>42wt.%, B2O3>24wt.%.

5. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 1, characterized in that: The purity of the gallstone in the anti-abnormal gelling material is required to be ≥90wt.%, and the chemical composition requirements are: CuO>28wt.%, SO3>28wt.%.

6. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 1 to 5, characterized in that: The abnormality-preventing gelling material is obtained by processing the following steps: S1. Mix 40-60 parts of ulexite, 20-40 parts of colemanite and 10-20 parts of boraxite evenly, crush them after mixing evenly, and control the crushing ratio to 40-70; grind the crushed mixed material into mixed fine material, and control the crushing ratio to 400-900; send the crushed mixed fine material to a high-temperature calcining furnace for calcination, and control the calcination temperature to 800°C-1500°C; the mixed material after calcination is quickly cooled to room temperature, and the cooling time is controlled to 10-20min; after cooling, obtain Class A mixed material; S2, mixing the Class A mixture prepared in step S1 with 5-15 parts of gallstones, and grinding the mixture to obtain a Class B mixture; the particle size requirements of the Class B mixture are Dx(10)≤5μm, Dx(50)≤14μm, and Dx(90)≤30μm; S3, subjecting the Class B mixed material to a coating treatment, specifically, adding the Class B mixed material to a coating solution, mixing evenly and reacting for a set time, and vacuum drying to obtain the abnormality-preventing gelling material.

7. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 6, characterized in that: The coating solution described in step S3 includes the following components by mass ratio: Anhydrous ethanol: phenolic resin: polymethyl methacrylate: dimethyl phthalate: diethyl phthalate = (55~70): (15~25): (5~10): (5~10): (5~10).

8. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 6, characterized in that: The concentration of the plating solution in step S3 is 55 wt.% to 85 wt.%.

9. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 6, characterized in that: In step S3, the dosage ratio of the type B mixture to the coating solution is 1:(5~20).

10. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 6, characterized in that: In step S3, the reaction time is set to 5-35 min; the vacuum drying temperature is 35° C.-55° C.

11. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 1 to 5, characterized in that: The reinforcing anti-decay material is a mixture of quartz sand and metakaolin, wherein the mass ratio is quartz sand: metakaolin = (80-90): (10-20).

12. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells as claimed in claim 11, characterized in that: The composition of the quartz sand is SiO2≥98 wt.%, and the powder fineness is ≥325 mesh; the composition of the metakaolin is Al2O3≥45wt.%, SiO2≥45 wt.%, and the powder fineness is ≥800 mesh.

13. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 1 to 5, characterized in that: The suspended fluid loss reducing material is a mixture of ultrafine calcium carbonate and dolomite fine powder, wherein the mass ratio of ultrafine calcium carbonate: dolomite fine powder is (30-70): (30-70).

14. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 13, characterized in that: The ultrafine calcium carbonate has a purity of ≥90wt.%, and a powder fineness of ≥800 mesh; the dolomite fine powder has a purity of ≥90wt.%, and a powder fineness of ≥1000 mesh.

15. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 1 to 5, characterized in that: The high temperature fluid loss reducer is an AMPS anionic polymer.

16. A new type of high temperature resistant cementing slurry system for 10,000-meter deep wells according to any one of claims 1 to 5, characterized in that: The high temperature retarder is an AMPS copolymer system.

Citation Information

Patent Citations

  • Cementing regulator for oil well cement

    CN110204236A

  • Suspension stabilizer for preventing abnormal high-temperature thickening of well cementation cement and preparation method of suspension stabilizer

    CN117142791A

  • Thickening time control agent for solving abnormal gelling and thickening time upside-down of high-temperature cement paste and preparation method of thickening time control agent

    CN117777970A